Ouvindo o silêncio: a construção identitária por meio da prática do mergulho scuba como consumo hedônico - Gomes, Maurício de Brito (2008)
This work aims to explore the context and emotions related to the experience of scuba diving as hedonic consumption, as well as to understand in which conditions the benefit arising from the regular practice of this activity impact the identity construction of the practitioner. Through in-depth interviews, data were collected from scuba divers living in the city of Rio de Janeiro, during the months of January and February of 2008. In order to obtain the expected objectives, the chosen methodology of research was qualitative, with priority of the subject and the subjectivity, using an interpretative approach for the data analysis. The research results confirm some benefits of high-risk sports practice such as flow, self-evolution and communitas. Two additional benefits are presented: the condition of alterity of the ¿underwater world¿, which attributes extraordinany meaning to scuba diving and impacts identity construction, and the scuba ¿buddy¿ practice, that helps to build-up an overall sense of trust to the other. The work is concluded with some managerial recommendations aiming the development of scuba diving industry and related tourism. These above mentioned suggestions include a new industry positioning, integrated marketing communications with specific references to alterity and flow, market segmentation, the creation of gathering spaces and a gradation scale among practitioners.